A study on the dynamic train-track interaction over cut-fill transitions on buried culverts. (September 2017) - Varandas, J.N.; Paixão, A.; Fortunato, E.
Highlights: This paper presents further developments to a three-dimensional numerical program suited to study railway transition zones. The paper focuses on a cut-fill-cut transition case, with a buried culvert included. The paper analyses the effect of the existence of the culvert in the dynamic system response. The paper analyses the effect of the longitudinal level irregularities in the long-term behaviour of the track transition. Abstract: Sudden changes in the structural and geotechnical properties of railway tracks along its course are normally associated with subgrade stiffness transitions, differential settlements and, ultimately, hanging sleepers that reduce the performance of the railway system. This paper aims at analysing and quantifying the impact of such situations, particularly cut-fill transitions combined with the presence of culverts, on the train-track system response. A cut-fill transition on a buried culvert is used as case study for which track geometry and stiffness evaluation data were available. A numerical model, considering the coupled train-track interaction, was developed using a 3D FEM dynamic analysis tool that was further improved here with a mixed implicit-explicit time integration scheme. The results suggest that the faster degradation rates typically found at similar locations are mostly related to the development of early permanent deformations in the subgrade layers, rather than to sudden stiffness transitions, which then aggravate the problem by causing important dynamic amplifications in the train-track interaction. Therefore, numerical approaches similar to the one presented herein can be valuable tools for designers and railway infrastructure managers in order to anticipate and mitigate such negative effects at these locations.